Estrategias de marketing para impulsar el crecimiento de la empresa Industrias Gráficas Brallec S.A.C. en la provincia de Trujillo. - Garcia Briones, Sara (2012)
The present investigation work has as objective to determine the Marketing Strategies to impel the growth of the company of Design Graph and Publicity Harvest in the County of Trujillo. With the purpose of to determine and to formulate the strategies of appropriate marketing you proceeded he/she is necessary to carry out the study, for that which through the method deductive and descriptive you determines the population’s sample in study, which was conformed by the existent publishers in the county of Trujillo. Likewise he/she is carried out analysis of the situation and demand of the service, of Design graph and Publicity and proceeded to formulate strategies of Marketing that Will allow to impel the growth of the company in the market. Of investigation and analysis is you concluded that the company doesn’t have a strategic plan of marketing; but through their qualified personnel it a service of quality, that which has allowed him to capture a market and to generate the client’s loyalty, in spite of the existent competition in the market. Being recommended this way to carry out a strategic plan marketing to be able to detect the changes in the environment and tendencies of the market; to be focused to use the marketing mixture; likewise activities planned to achieve the recognition and growth of the company in the market.